Discovering the best: Informational efficiency and liquidity of alternative trading mechanisms in experimental asset markets - Andreas Oehler; Klaus Heilmann; Volker Läger (Otto-Friedrich-Universität Bamberg, Lehrstuhl für Betriebswirtschaftslehre, insbesondere Finanzwirtschaft, 2001)
This paper reports the results of 18 experimental asset markets with 262 subjects that explore the effects of liquidity and aggregation of information. The main focus lies on the comparison of different trading mechanisms of stock exchanges. Compared to most of financial markets experiments, reality is met by introducing long-living assets and integrating all subjects in a multi-period decision-making process. In accordance with the evidence from the empirical research in real financial markets, our results show that the continuous auction achieves the highest informational efficiency. Dealer markets do the worst; call markets (batch trading) reach an intermediate position. A comparable result is achieved regarding the liquidity of the trading mechanisms. For both success factors of real stock exchanges our results show a strong tendency that continuous trading outperforms the other market structures, at least in the framework of the present measurement and on the chosen abstraction level. This does not exclude for the practice to offer a combination with call markets in certain titles and at certain times, particularly, if the here met assumptions of an open market access and information symmetry between the investors do not apply in full extent.
Keywords: D44; G14; G12; 330; Market Microstructure; Experimental Asset Markets; Market Efficiency; Informational Efficiency; Liquidity; Call Markets; Continuous Auction; Börsenkurs; Börsenumsatz; Wertpapierhandel; Börsenspiel; Mikrostrukturanalyse; Informationseffizienz